Journalism Ethics in Quranic Perspective: [Etika Jurnalistik Perspektif Al-Qur’an] - Sauda, Limmatus (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
Today, journalistic world increasingly finds its freedom. effects can no longer be taken lightly. Therefore, there should be some rules to control and to command the journalists, not to restrict it. Related to this issue, the normative sources of Islam, the Qur’a, such as found in (QS. al-Ahzab [33]: 70), encourage people to speak the truth honestly. In another verse, Allah also ordered to stay away from the prejudice that would bring doubt and untruth (QS. al-Hujurat [49]: 12), nor slander broadcast news in various forms (QS. al-Nur [24]: 19). In addition, the reader should check the truth first before receive it (QS. al-Hujurat [49]: 6). Some of these verses are references to the news makers or journalists in their works, as well as for the consumers when they receive the news. In this paper, the dialogue between the Qur’an and the phenomenon of journalism displayed using the comparative nature of the interconnection pattern (in this case the journalistic ethics of the Press Council and the decision of the Indonesian Broadcasting Commission and journalistic ethics in the Qur’an). Concerning the exegesis of the Qur’an, the method is used is ijmali and it did not interpret all of the content of verses, only part of it related to the news. [Hari ini, dunia jurnalistik semakin menemukan kebebasan. Dampaknya tidak bisa lagi dianggap enteng. Oleh karena itu, harus ada aturan untuk mengendalikan dan mengatur jurnalistik, walaupun hal itu tidak dimaksudkan untuk membatasi. Terkait dengan masalah ini, sumber-sumber normatif Islam, al-Qur’an, seperti yang ditemukan dalam (QS. al-Ahzab [33]: 70), mendorong orang untuk berbicara kebenaran jujur. Dalam ayat lain, Allah juga memerintahkan untuk menjauh dari prasangka yang akan membawa keraguan dan ketidakbenaran (al-Hujurat [49] QS. 12). Atau fitnah siaran berita dalam berbagai bentuk (QS al-Nur [24]: 19). Selain itu, pembaca harus memeriksa kebenaran terlebih dahulu sebelum menerimanya (QS al-Hujurat [49]: 6). Beberapa ayat-ayat ini adalah referensi kepada para pembuat berita atau wartawan dalam karya-karya mereka, serta bagi konsumen ketika mereka menerima berita. Dalam tulisan ini, dialog antara Al-Qur’an dan fenomena jurnalisme ditampilkan menggunakan sifat komparatif pola interkoneksi (dalam hal ini etika jurnalistik Dewan Pers dan keputusan Komisi Penyiaran Indonesia dan etika jurnalistik dalam Qur’an). Mengenai tafsir Al-Qur’an, metode yang digunakan adalah ijmali dan tidak menafsirkan semua isi ayat, hanya bagian dari itu berkaitan dengan berita.]